Economic theory and the underdeveloped countries - Myint, Hla (New York, Oxford University Press, 1971)
The papers collected in this volume are concerned with the middle level of analysis between pure formal economic theory and detailed empirical studies of particular underdeveloped countries. Their aim is to examine the realism and the relevance of theoretical concepts and doctrines, both orthodox and modern, in relation to the broadly observable patterns of economic change, the salient features of the economic situation, and the general aims of development policy in the underdeveloped countries.
Essays.
rpm 05/10/2017
Loans
Keywords: Economic development; Developing countries